Transcriptomic and metabolomic analyses unravel the different pathogenic mechanisms of Ustilaginoidea virens in indica and japonica rice - Fu, Rongtao; Chen, Yu; Chen, Cheng; Wang, Jian; Zhao, Liyu; Lu, Daihua (Frontiers in Microbiology, 2025)
Rice false smut (RFS) caused by the fungal pathogen Ustilaginoidea virens (Cook) produces high yield losses in rice. Rice varieties differ in their resistance to RFS. However, the pathogenic mechanism of the fungus U. virens in different varieties remains unclear. In our study, transcriptome and metabolome analyses were performed on U. virens after 5 and 7 days after infection in indica and japonica rice to reveal different pathogenic mechanisms. Interestingly, we discovered that the average number of diseased grains of the susceptible variety “GuiChao2” (indica rice) was higher than that of the susceptible variety “Zhejing99” (japonica rice) under the same inoculation conditions. In all, 6,073, 5,795, 4,251, and 5,978 differentially expressed genes (DEGs) were shared among the four infected rice compared with the control group. In this study, there were differences in the types and quantities of transcription factors in U. virens after infection of indica and japonica rice. A Kyoto Encyclopedia of Genes and Genomes analysis showed that the DEGs involved in the mitogen-activated protein kinase signaling pathway, autophagy–yeast, lysine biosynthesis, phenylalanine metabolism, and tryptophan metabolism responded to infection, and the expression patterns of key regulatory genes, including STE, ATG, CYP, and LYS differed after infection indica and japonica rice. The results of a metabolome analysis indicated that the differentially accumulated metabolites (DAMs) mainly were significantly enrichment in pathways included amino acids, lipids, and nucleosides, and the accumulation patterns between infected indica and japonica rice differed. Furthermore, the combined transcriptome and metabolome analysis revealed that different DAMs regulated by different DEGs produced variations in the pathogenicity of U. virens infection in indica and japonica rice. Hence, this study provides insight into the molecular mechanisms related to U. virens infection in different rice varieties.